Gender role attitudes in Germany, 1982-2016: An age-period-cohort (APC) Analysis - Daniel Lois (Comparative Population Studies (CPoS), 2020)
The present study investigates the change of gender role attitudes in Germany between 1982 and 2016. Nine waves of the German General Social Survey are used (N = 26,389). In contrast to previous trend studies, which largely ignore age effects, a mechanism-based age-period-cohort model ( Winship/Harding 2008) is applied. It becomes clear that age, period and cohort independently have an impact on gender role ideology. Compared to earlier research, new insights concerning the shape of cohort effects come to light: Specific to traditional gender ideology in Western Germany, it is apparent that the trend towards increasingly egalitarian attitudes comes to a halt in men born around 1956 and later and in women born 1966. For Eastern Germany we observe that the cohort-specific trend towards liberalisation in younger cohorts either is diminishing or even tends to reverse. This pattern of effects mainly mirrors the phases of the feminist movement in Western Germany and the rise and decline of the German Democratic Republic, respectively.
urn:nbn:de:bib-cpos-2020-02en9
Keywords: 300; APC analysis; Identification problem; Sexism; Gender role attitudes; German reunification